Stress Characteristics and Cheating Tendencies Among Primary Learners in Calabar South Nigeria - Okon, Maureen Okang (American Journal of Education and Learning, 2016)
The study investigated the relationship between stress characteristics (academic, financial and personal social) and cheating tendencies among primary school learners. The survey design was adopted for the study. The stratified random sampling technique was used in selecting 300 pupils for the study. Two null hypotheses were formulated to guide the study. A survey instrument called SCACTQ with thirty-two (32) items duly validated was used for data collection. Data was analyzed using Pearson product moment correlation analysis for hypothesis 1 and independent test for hypothesis 2. Result of data analysis revealed significant relationship between stress (academic, financial personal social) and cheating tendencies of pupils. Result also suggested that sex difference influences stress and cheating tendencies of pupils.